Características físicas e fisiológicas de Aquênios de Lychnophora ericoides Mart. (Arnica-do-campo) de uma população ocorrente na serra da Bocaína, região do Alto Paranaíba, Minas Gerais - Lopes, Susana Weber (2008)
Lychnophora ericoides is a shrub like species, endemic to rock outcrops areas, whose cultivation practices are unknown and its irregular maturation being the great problem for seedling production. The objective of the work was to evaluate the germination of L. ericoides cypsela collected from across different altitudes of a population occurring in the Serra da Bocaina, region of Alto Paranaíba, Minas Gerais, and submitted to methods for cypselas selection with relation to density. In the first experiment, arnica capitulum of 20 access (altitudes between 1102 and 1245m) formed a completely randomized design, with 20 access (treatments) and four repetitions, in groups with 50 cypselas removed from the borders of the capitulum. In the second experiment, samples of the same cypselas were placed in a blower for 3 minutes and 20 seconds, the heaviest being separated in two groups. Half of the cypselas were washed in running water for 24 hours and the other half were submerged in sulfuric acid for 1 minute and soon after washed in running water for 24 hours. After the separation, the germination test was set up in a completely randomized design in factorial scheme of 2 x 20, the first factor corresponding to treatments (water and sulfuric acid) and the second factor, to the 20 access in four repetitions containing 50 cypselas. In both experiments, the cypsela were distributed in gerbox containing blotting paper humidified with distilled water, being counted, first the cypselas germinated in function of the protrusion of the radicle and, in the second, normal seedlings. In the first experiment, the cypselas presented low percentage of germination (maximum 15%). The small difference between the germination percentage and viability indicated that few cypselas at the end of the germination test were viable, a result proven by the high percentage of empty cypselas (above 65.5%). The percentage relative to germination (full cypselas) showed high capacity of cypsela germination (72.38, 78.13 and 66.85% for cypselas from access 1, 3 and 5, respectively). The variation of the altitude gradient of 143 m was not lineally related to the presence of empty seeds, not even to the physiologic quality of the cypselas. The cypsela germination was slow and distributed over time. After the density test, the maximum germination was also low (maximum 34% for the access 2 submitted to sulfuric acid). The use of sulfuric acid after the density test, in a general way, improved the quality of the cypselas and increased the percentage of cypsela germination of same.